Orbital‐ to millennial‐scale variation of the speleothem δ 18 O record during Marine Isotope Stages 5 to 3 on the southeast Chinese Loess Plateau and its climatic and environmental implications - YANJUN CAI; HAI CHENG; XING CHENG; ZHENGGUO SHI; YANBIN LU; LE MA; CARLOS PÉREZ‐MEJÍAS; HAIWEI ZHANG; YINGYING WEI; GANG XUE; HANYING LI; MEI HE; et al. (Journal of Quaternary Science, 2023)
The Chinese Loess Plateau (CLP) is located in northern China, a region climatically dominated by the East Asian monsoon. Speleothem records from this region are crucial to fully understand the variability of the East Asian summer monsoon (EASM) and reconcile the disparity seen between loess records and speleothem δ 18 O records for the EASM. Here, we present an absolutely dated stalagmite isotope record spanning most of Marine Isotope Stage (MIS) 5 to MIS 3 from Xiaotian Cave, southeast CLP. The Xiaotian speleothem δ 18 O record is dominated by precessional variations and punctuated by notable millennial‐scale oscillations; in particular, the δ 18 O values in MIS 5e, 5c and 5a were in the same range, consistent with other speleothem δ 18 O records from the EASM region within quoted errors, verifying the difference between speleothem δ 18 O and loess records (e.g. magnetic susceptibility) and the proposition that those two archives may record different aspects of the EASM changes. The similar values in MIS 5e, 5c and 5a observed from the speleothem δ 18 O records in EASM regions, incompatible with the relatively higher North Hemisphere Summer Insolation (NHSI) during MIS 5e, were probably caused by an equivalent or even increased contribution of 18 O‐enriched moisture from the South China Sea and North Pacific, implying that an El Niño‐like state existed during MIS 5e. The Xiaotian δ 18 O values increased abruptly at ~121.7 thousand years (kyr) before the present ( bp , present refers to ad 1950), consistent with the trend seen in previously reported Chinese speleothem δ 18 O records, indicating an abrupt regime shift in atmospheric circulations or hydroclimate conditions in the Asian monsoon systems. It cannot be definitely ruled out that an increase in sea ice extent in the northern North Atlantic, responding to a decrease of NHSI, reached a threshold to have led to abrupt changes in the Asian summer monsoon (ASM) through rapid shifts in the position of circulation of the westerlies and/or in the position of Intertropical Convergence Zone (ITCZ). Here, we hypothesized that sea surface cooling in the tropical Indian and Pacific Ocean caused by the decreased summer insolation reached a threshold that eventually resulted in an abrupt shift to more positive precipitation δ 18 O, either through weakened convection over the tropical ocean, or through abrupt shifts in moisture transport and cycling of tropical moisture sources for the ASM. The Xiaotian speleothem δ 18 O record also shows centennial‐scale variability with amplitude up to 3‰ within MIS 5e. These changes are similar to variations recorded by the speleothem δ 18 O record from Tianmen Cave on the south‐central Tibetan Plateau and Shangxiaofeng Cave in Shandong Province, northern China, suggesting a heightened sensitivity of precipitation δ 18 O to climate changes at the marginal zone of the ASM even during the warm and humid MIS 5e interglacial. Climatic oscillations during MIS 5e appear to be comparable to those typical of the Holocene, implying rather unstable climate conditions during the Last Interglacial.